2010
DOI: 10.1038/sc.2009.195
|View full text |Cite
|
Sign up to set email alerts
|

The clinical study of repairing cauda equina fibres with fibrin glue after lumbar fracture and dislocation

Abstract: Study design: A retrospective study. Objectives: To study the outcome of repair of cauda equina fibres with fibrin glue after lumbar fracture and/or dislocation. Methods: Seven acute cases and one chronic case of L2 or L3 fracture and/or dislocation complicated with complete cauda equina injury were selected. Sural nerve or ventral roots of injured cauda equina were chosen to repair the motor cauda equina fibres with fibrin glue after open reduction and internal fixation of the unstable vertebrae. The function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently, it has been shown that tissue glue can be used to repair the nerve fi bers and may be associated with better neurological recovery. 12 This may be explained by the fact that the cauda equina is more similar to the peripheral nervous system, with a higher potential for neurological recovery compared with the spinal cord. In these patients, the cauda equina fi bers may be crushed, torn, or lacerated by the bony fragments.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, it has been shown that tissue glue can be used to repair the nerve fi bers and may be associated with better neurological recovery. 12 This may be explained by the fact that the cauda equina is more similar to the peripheral nervous system, with a higher potential for neurological recovery compared with the spinal cord. In these patients, the cauda equina fi bers may be crushed, torn, or lacerated by the bony fragments.…”
Section: Resultsmentioning
confidence: 98%
“…However, because nerve roots within the cauda equina lack an epineurium (i.e., the connective tissue around peripheral nerves), directly repairing nerve roots with suture is difficult, if not impossible. Fibrin glue may be beneficial in cases where a limited gap between stumps exists . However, high tensile forces have been shown to hinder neuronal regeneration, and nerve root stumps are prone to retraction after transection.…”
Section: Discussionmentioning
confidence: 99%
“…Intradural repair allows the surgeon to minimize the injury site gap, optimize the alignment of proximal and distal stumps, and manipulate the environment at the lesion into one more conducive to axonal regeneration through the implantation of grafts, scaffolds, anti‐scarring compounds, or other growth‐promoting agents. However, given the prognostic uncertainty that surrounds many cauda equina injuries and the paucity of established treatments, attempts at intradural repair of injured nerve roots are exceptionally rare . A more common approach involves spinal stabilization and decompression of the canal space .…”
mentioning
confidence: 99%
“…This is a very interesting paper from Sun et al 1 Repairing injured nerve roots is a rarely reported topic. In a certain way, it can be compared with the repair of intracranial nerves, with regard to which it has been shown that repair of transacted nerves can be followed by a successful and, for a patient, useful recovery of the function.…”
mentioning
confidence: 99%